2013
DOI: 10.4244/eijv8i10a176
|View full text |Cite
|
Sign up to set email alerts
|

Adverse event rates following primary PCI for STEMI at US and non-US hospitals: three-year analysis from the HORIZONS-AMI trial

Abstract: In the HORIZONS-AMI trial, STEMI patients undergoing primary PCI at US versus OUS sites had higher rates of adverse events, which persisted after adjusting for baseline risk. The reasons for these differences are not clear but may be due to unmeasured confounders, different thresholds for event reporting, or valid differences in systems of care and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 12 publications
2
15
0
3
Order By: Relevance
“…To the best of our knowledge, this study is the first and largest to compare the rates of in‐hospital mortality between STEMI patients with and without LVT. The overall mortality rates in STEMI (7.7% w/LVT vs 8.5% w/o LVT) in our study are comparable to reported 30‐day mortality rate, of 2.5%‐10% in patients admitted with STEMI …”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, this study is the first and largest to compare the rates of in‐hospital mortality between STEMI patients with and without LVT. The overall mortality rates in STEMI (7.7% w/LVT vs 8.5% w/o LVT) in our study are comparable to reported 30‐day mortality rate, of 2.5%‐10% in patients admitted with STEMI …”
Section: Discussionsupporting
confidence: 88%
“…Providers and patients may have been less willing to alter therapy in patients who had been clinically stable on standard dose clopidogrel therapy after ACS/PCI. Given that the risk of recurrent adverse cardiovascular events and stent-related complications is highest in the first 30 days after ACS or PCI, 22,23 our findings likely underestimate the response to CYP2C19 genetic testing when it is used for patients with more acute coronary artery disease. Patient factors such as the higher cost of branded antiplatelet agents and the increased risk of bleeding complications with alternative antiplatelet therapy may have also contributed to our findings.…”
Section: Discussionmentioning
confidence: 81%
“…However, with the advent of potent oral P2Y 12 receptor inhibitors, GPIs are less frequently used in Europe, and the bleeding advantage with bivalirudin versus UFH alone is likely of lesser magnitude than with bivalirudin versus UFH plus GPI. Moreover, because of its short half-life, stopping bivalirudin at the end of the PCI procedure was associated with an approximate 1% increase in acute (<24 hours) stent thrombosis in patients with STEMI in HORIZONS-AMI, although mortality was reduced at 30 days with bivalirudin (2.1% vs 3.1%, p=0.04), a difference which persisted for 3 years 80. An increase in acute stent thrombosis after discontinuation of bivalirudin has not been observed in NSTE-ACS.…”
Section: Anticoagulationmentioning
confidence: 99%